Association of BMI measurements to waist circumference and waist-to-height ratio in overweight and obese children - Sindy Irenewati; Nahwa Arkhaesi; Wistiani Wistiani (Indonesian Pediatric Society, 2020)
Background Early monitoring of visceral fat is important to prevent the worsening of obesity in children. In recent years, waist circumference (WC) and waist-to-height ratio (WHtR) measurements have gained attention as an anthropometric indexes for obesity in children. They are an easy-to-use, inexpensive, specific to visceral fat and safe monitoring methods for children. International reference values, however, do not exist for any of the two measures to determine obesity in children. Objective To compare WC and WHtR to body mass index (BMI) status in overweight and obese children aged 10-12 years. Methods This cross-sectional study included overweight and obese children aged 10-12 years from four primary schools in Semarang, Central Java. Subjects underwent anthropometric measurements including weight, height, and waist circumference. Subjects were classified as obese (>=P95) or overweight (P85<=P<P95) using BMI percentiles according to age and sex. Chi-square test was used to assess for associations between categorical variables and multivariate logistic regression analysis was used to identify a dominant variable. Results Forty-two obese and 23 overweight children were studied. Children with higher values of WC (PR=1.879) and WHtR (PR=8.352) had a higher prevalence of having higher BMI status (obese). Using multivariate analysis, WHtR was the more dominant variable associated with BMI status, compared to WC. Conclusion Higher WC (cut off P90) and WHtR (cut off 0.5) have a significant associations with greater obesity children aged 10-12 years. Compared to WC, WHtR is a stronger predictive factor for obesity.